Setting up of on-grid solar photovoltaic system strategies formulation through scenario planning - Planas, Jaime B. (University of the Philippines Diliman, Technology Management Center, 2012)
Energy fuels an economy. It is an important ingredient to the country's economic growth and drive towards global competitiveness leading to sustainable progress for poverty reduction and social equity. The Philippines is endowed with indigenous renewable energy resources which include biomass, geothermal, SOLAR energy, hydropower, ocean power and wind power. This paper entitled "Setting up of On-grid Solar Photovoltaic System : Strategies Formulation Through Scenario Planning" provides an outlook of the development process of an On-grid Solar Photovoltaic Project highlighting the critical factors which include : social, technological, environmental, economic and political dynamics. It aims to dissect the aforementioned factors which are valuable pieces of information for fledging companies and project developers alike, to consider prior to venturing in the business of power generation with particular focus on Solar Photovoltaics. The key project proponents are : Department of Energy-Renewable Energy Management Bureau; Local Government Unit of Porac, Pampanga; Pampanga II Electric Cooperative, Inc.; National Grid Corporation of the Philippines; Philippine Atmospheric Geophysical Astronomical Services Administration and Department of Environment and Natural Resources - Environmental Management Bureau. Valuable inputs, processes and documentary requirements needed to pursue the project will be presented and considerably discussed. A review of literatures on Photovoltaic Technology, Social Shaping of Technology and Scenario Planning along with the conduct of on-site interviews will complete the methodology employed in the paper. As a result, various scenarios will be described, strategies formulated, conclusions defined and recommendations explained.